Urgensi Manajemen Bimbingan Konseling dalam Melahirkan Peserta Didik Berkarakter - Robiatur Rohmah (Jurnal Pendidikan Islam Indonesia, 2019)
The success of education in schools is determined by the managerial abilities of the headmaster. The performance of school management will determine the success of the school in carrying out the programs. In this context, counseling management is important to create students with noble character. Character building is very much influenced by the characteristic of the environment. Therefore, creating a helpful environment with the appropriate counseling management will significantly influence the education quality improvement in moral values both inside and outside of school. Character building is a lifetime process that must be sustained in school, family, and society to internalize the character building.